ANALYSIS OF MARKETING STRATEGY OF OREO THROUGH BRAND AWARENESS AND EFFECT ON MARKETING PERFORMANCE AT PT. MONDELEZ INDONESIA IN MAKASSAR - Zubair, Muh; Kadir, Abd Rahman; Reni, Andi (Universitas Muhammadiyah Luwuk Banggai, 2023)
This study aims to analyze the marketing strategy of Oreo biscuit products through brand awareness and its effect on marketing performance at pt. Mondelez Indonesia in Makassar. The population in this study is all PT Mondelez Indonesia outlets in Makassar which amounted to 1209 outlets. While the sample taken in this study used Slovin. This is because the population size is known and normally distributed. Data collection techniques were used by distributing questionnaires and data analysis in this study using the Partial Least Square (PLS) method. The results of this study show that factors such as product, price, place, and promotion have a positive and significant influence on brand awareness and marketing performance at PT. Mondelez Indonesia in Makassar. However, brand awareness is not always able to mediate the influence of product, price, place and promotion on marketing performance. Nevertheless, brand awareness still has an important role in influencing marketing performance directly